2013
DOI: 10.1007/s13187-013-0471-3
|View full text |Cite
|
Sign up to set email alerts
|

Health Literacy, Health Communication Challenges, and Cancer Screening Among Rural Native Hawaiian and Filipino Women

Abstract: Native Hawaiians and Filipinos are disproportionately impacted by cancer, and are less likely to participate in cancer screening than whites. Limited information exists about health information pathways and health communication challenges as they relate to cancer screening in these groups. Six focus groups (n=77) of Native Hawaiian and Filipino women age 40+ years were conducted to investigate these research gaps. Participants noted many health information challenges. Challenges were both practical and interpe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 16 publications
1
12
0
Order By: Relevance
“…On balance, racial and–ethnic minorities and women of lower socioeconomic status were less likely to have a good understanding of prenatal testing options and of their own experience. These data parallel reports documenting disparities in various screening domains 15-19 . While the American College of Obstetricians and Gynecologists recommends that “...screening and invasive diagnostic testing for aneuploidy should be available to all women...regardless of maternal age” 20 , it appears that this information is not being effectively provided to all women, and that many do not understand the messages conveyed.…”
Section: Discussionsupporting
confidence: 83%
“…On balance, racial and–ethnic minorities and women of lower socioeconomic status were less likely to have a good understanding of prenatal testing options and of their own experience. These data parallel reports documenting disparities in various screening domains 15-19 . While the American College of Obstetricians and Gynecologists recommends that “...screening and invasive diagnostic testing for aneuploidy should be available to all women...regardless of maternal age” 20 , it appears that this information is not being effectively provided to all women, and that many do not understand the messages conveyed.…”
Section: Discussionsupporting
confidence: 83%
“…33 Other investigators conducting focus groups of minority women have highlighted the importance of family, friends, and community in understanding and disseminating health-related information as well as the desire for a local community context in health communication. 34 Our finding that health literacy did not differ between persons with more or less trust in the information provided by their doctor was not surprising. Gutierrez et al 35 showed that level of health literacy did not impact patient's reliance on their healthcare providers to obtain health information in the primary care setting.…”
Section: Discussionmentioning
confidence: 66%
“…With the increased interest in ageing‐in‐place initiatives, this finding can be applied to the development of community‐based strategies aiming to support older immigrants in staying healthy and remaining independent. Peers could play a critical role in health behaviour changes in populations with health disparities (Sentell, Dela Cruz, Heo, & Braun, ). To enhance their adherence with treatment regimens and recommendations directed by their HCPs, a peer‐based health education programme can be developed and implemented among this population.…”
Section: Discussionmentioning
confidence: 99%